New approaches to defense inflation and discounting - Connor, Kathryn L.; Dryden, James A.; Rand eBooks (Santa Monica, CA : RAND, 2013)
Inflation indices and discount rates are necessary tools in the Department of Defense$1 (Bs (DoD$1 (Bs) acquisition process, as the final selection of a system is partially based on potential increases in sustainment costs (inflation) and the present value of future costs (discounting). Inflation indices built for DoD use very broad categories that include operations and maintenance (O&M) as well as manpower, procurement, and research and development. This study addresses the question of how well current inflation indices and discount rates are serving DoD weapon-system program management. It investigates inflation rates for parts for the Abrams tank and the Bradley armored personnel carrier and shows that the two weapon systems, while both ground systems, experience inflation differently. Although government decisionmaking can benefit from discounting (taking into account the time value of money), choices made using discounted cash flows are not always the least expensive for DoD. Its O&M estimating strategies should be reviewed to reflect changing repair and other costs, since a range of reasonable courses of action exists for many DoD investment decisions. Recommendations for the Office of Cost Assessment and Program Evaluation to consider when evaluating the inflation and discounting policies that impact the long-term affordability of DoD programs include (1) revisiting O&M costs annually with a 5-year moving-average inflation, to reflect changing repair and other costs; (2) highlighting the role of supply chain surcharges in parts costs in cost estimates used to inform program financial analysis; (3) expanding analysis of investments to ensure consideration of least-cost outcomes.s
Introduction -- Cost Inflation of Ground-Vehicle Parts -- The Value of Discounting -- New Approaches to Inflation and Discounting -- Appendix: Inflation Estimates over Time.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 41-42).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Department of Defense -- Appropriations and expenditures -- Effect of inflation on; United States. -- Department of Defense -- Procurement; Armored vehicles, Military -- United States -- Costs; Electronic books